The impact of the COVID-19 pandemic on the use of social media: A cross-national comparison - Franco Delogu; Kineta Morgan-Paisley; Claudia Del Gatto; Allegra Indraccolo; Tiziana Pedale; Riccardo Brunetti (Acta Psychologica)
This study investigates the impact of limited interpersonal interaction due to the COVID-19 pandemic on social media usage in the USA and Italy, considering their differences in lockdown restrictions. An online survey with 1478 participants assessed social media usage, personality traits, and life satisfaction before the pandemic (2018) and during the first lockdown (April 2020). Results showed increased social media use during the pandemic, with no significant differences between countries. Personality traits like extraversion were linked to higher social media usage, while emotional stability was negatively correlated. The study highlights that while social media served as a coping mechanism, its passive use could contribute to negative emotional states, raising concerns about mental health during crises. Full-time employees showed a more pronounced increase in usage than students, likely due to increased free time and social isolation. Active engagement on social media did not significantly increase, suggesting a tendency towards passive content consumption. These findings underscore the complex interplay of demographic, psychological, and situational factors influencing social media use during the pandemic.